2023
DOI: 10.1001/jamanetworkopen.2023.15074
|View full text |Cite
|
Sign up to set email alerts
|

Inequities in Filled Overactive Bladder Medication Prescriptions in the US

Abstract: ImportanceAnticholinergic medications to treat overactive bladder (OAB) have been associated with increased risk of cognitive decline, whereas β3-adrenoceptor agonists (hereafter, β3-agonists) have comparable efficacy and do not carry the same risk. Yet, anticholinergics remain the predominant OAB medication prescribed in the US.ObjectiveTo evaluate whether patient race, ethnicity, and sociodemographic characteristics are associated with receipt of anticholinergic vs β3-agonist OAB medications.Design, Setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…While the literature evaluating coverage trends for OAB medications is limited, prior studies have shown higher out-of-pocket costs for beta-3 agonists compared with anticholinergics consistent with the findings in this study. Luchristt et al 23 demonstrated a median out-of-pocket cost for 1 insurer of $45 per fill for beta-3 agonists versus $9.78 for anticholinergics. They also showed that fulfillment of beta-3 agonist medications is disproportionately low in non-Hispanic African American populations compared with White populations suggesting that these coverage trends likely further exacerbate known inequalities in health care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature evaluating coverage trends for OAB medications is limited, prior studies have shown higher out-of-pocket costs for beta-3 agonists compared with anticholinergics consistent with the findings in this study. Luchristt et al 23 demonstrated a median out-of-pocket cost for 1 insurer of $45 per fill for beta-3 agonists versus $9.78 for anticholinergics. They also showed that fulfillment of beta-3 agonist medications is disproportionately low in non-Hispanic African American populations compared with White populations suggesting that these coverage trends likely further exacerbate known inequalities in health care.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that fulfillment of beta-3 agonist medications is disproportionately low in non-Hispanic African American populations compared with White populations suggesting that these coverage trends likely further exacerbate known inequalities in health care. 23 In their evaluation of Medicare beneficiaries, Shapiro et al 24 similarly reported differences for coverage for generic anticholinergics with total yearly costs for IR n AUGS SPECIAL ISSUE SUBMISSION…”
Section: Discussionmentioning
confidence: 99%